Fundamentals of corporate finance - Ross, Stephen A. (McGraw-Hill/Irwin, 2013)
The Tenth Edition continues the tradition of excellence that has earned Fundamentals of Corporate Finance its status as market leader. Every chapter has been updated to provide the most current examples that reflect corporate finance in today’s world. The supplements package has been updated and improved, and with the enhanced Connect Finance and Excel Master, student and instructor support has never been stronger.